The Mediating Role of Financial Health on the Relationship Between Financial Personality Types, Credit Dependency, and Financial Preparedness for Emergencies among SUCs Educators: Basis for a Program - Nepthali Bacones (Future Science / FSH-PH Publications, 2026)
Due to the importance of financial preparedness for emergencies (FPE) in individuals’ financial emergency-resiliency, this study examined the mediating role of financial health (FH) on the relationship between financial personality types (FPT), credit dependency (CD), and financial preparedness for emergencies (FPE). Utilizing Yamane’s formula and purposive-convenience sampling, three hundred fifty-two respondents took part in the study, representing the population of educators from selected State Universities and Colleges (SUCs) from Luzon, Visayas, and Mindanao in the Philippines. Descriptive, exploratory factor analysis, Pearson’s Moment Correlation, regression, and partial least squares structural equation modeling (PLS-SEM) were used to analyze the data. The results of the EFA have identified five FPT of SUCs educators. In addition, the result reveals a low level of CD, a good level of FH, and a moderate level of FPE. Moreover, FH fully mediates the relationship between FPT, CD, and FPE. The findings can be used as a basis for the formulation of a program that will help educators enhance their financial resilience by improving their FH, maintain low level of CD through wiser financial behavior in accordance with their respective FPT, and improving FPE.